FLOOD RISK KNOWLEDGE AND COMMUNITY PREPAREDNESS IN KAMPUNG BINA BARU, BIMA CITY: A QUALITATIVE STUDY - Muhammad Malthuf; Nety Fathuljannah (SOCIETY, 2024)
Hydrometeorological disasters frequently impact Indonesia, with floods constituting a recurrent threat, including in Bima City. The persistent occurrence of flooding in Kampung Bina Baru, Kelurahan Dara, primarily stems from high rainfall intensity, deforestation, and ineffective waste management. This study aims to analyze the residents' level of knowledge regarding flood disasters and identify the influencing factors. Employing a qualitative descriptive approach under a naturalistic paradigm, data collection was conducted via observation, interviews, and documentation. Data analysis encompassed reduction, presentation, verification, and conclusion drawing, while data validity was ensured through triangulation techniques. Findings indicate a generally low level of disaster preparedness knowledge among residents, primarily due to limited outreach and training on flood mitigation. Key influencing factors include internal elements such as education, occupation, age, and gender, and external elements such as infrastructure, socio-cultural conditions, and environmental context. Enhanced disaster education and community-based preparedness programs are critical for bolstering local resilience.Keywords: Knowledge, Risk, Flood Disaster, Bima City